DANCR promotes HCC progression and regulates EMT by sponging miR‐27a‐3p via ROCK1/LIMK1/COFILIN1 pathway. (30th April 2019) - Guo, Dan; Li, Yarui; Chen, Yifei; Zhang, Dan; Wang, Xin; Lu, Guifang; Ren, Mudan; Lu, Xinlan; He, Shuixiang
Abstract: Objectives: This research aims to verify that the long non‐coding RNA differentiation antagonizing nonprotein coding RNA (LncRNA DANCR) could modulate the proliferation and metastasis of hepatocellular carcinoma (HCC), and it thus may work as a novel biomarker to render new orientation for early diagnosis and clinical therapy of HCC. Materials and methods: Firstly, qRT‐PCR was used to detect the expression of genes including LncRNA DANCR and miR‐27a‐3p. Next, MTT assay, Ethynyldeoxyuridine (EdU) analysis and clone formation assay were used for investigating cell growth and proliferation. Meanwhile, transwell assay and wound healing assay were applied to evaluate the capacity of cell metastasis and motility, respectively. In addition, bioinformatic analysis and dual‐luciferase reporter assay were applied to analyse molecular interaction. Next, we conducted immunofluorescence and Western blot for mechanic investigation. Last but not the least, xenograft tumours in nude mice were built by subcutaneously injecting Hep3B cells stably transfected with sh‐NC and sh‐DANCR to detect proliferation and SMMC‐7721 cells stably transfected with sh‐NC and sh‐DANCR to investigate metastasis. Results: The results of qRT‐PCR and bioinformatic analysis revealed the high expression of DANCR in HCC. DANCR accelerated proliferation and metastasis of HCC cells and the knockdown of DANCR had the opposite effect. Meanwhile, xenograft tumours in sh‐DANCR group grow slower and have smaller volumes compared with negative control group. Next, the antineoplastic effect of miR‐27a‐3p on cell growth and motility of HCC was confirmed. In addition, we clarified that DANCR acted as a ceRNA to decoy miR‐27a‐3p via mediating ROCK1/LIMK1/COFILIN1 pathway. In the end, we validated that DANCR/miR‐27a‐3p axis regulates EMT progression by cell immunofluorescence and Western blot. Conclusions: In a word, DANCR promotes HCC development and induces EMT by decoying miR‐27a‐3p to regulate ROCK1/LIMK1/COFILIN1 pathway.